The bidirectional selection and shared adaptation mechanisms of tumor organ-specific metastasis - WANG Xing, XIAO Ruiling, BAI Jialu, JIANG Decheng, ZHOU Feihan, LUO Xiyuan, TANG Yuemeng, ZHAO Yupei (Zhongguo aizheng zazhi, 2025)
Metastasis is a pivotal and intricate process in the progression of malignant tumors, strongly correlating with poor prognosis. Approximately 90% of cancer-related mortality is attributed to metastasis, with the five-year survival rate for patients with metastatic solid tumors ranging from 5% to 30%. Consequently, a comprehensive understanding of the underlying biological mechanisms driving metastasis is essential for unraveling its core processes and developing novel therapeutic strategies. The metastatic cascade involves tumor cells navigating numerous biological barriers, including detachment from the primary tumor, invasion of blood vessels or lymphatics, survival in circulation, extravasation into distant organs and subsequent adaptation to the microenvironment. To surmount these challenges, tumor cells undergo phenotypic changes, genetic mutations and dysregulating signaling pathways. Additionally, microenvironmental factors (such as angiogenesis, matrix remodeling and immune evasion) play a critical role, orchestrating the initiation and growth of metastatic lesions in an interdependent manner. Organ-specific metastasis, a distinct subset of metastasis, involves dynamic bidirectional interactions between tumor cells and the microenvironment of target organs. These interactions determine the selectivity of metastatic spread and drive the adaptive evolution of both the tumor and the organ, which encompasses multiple layers of cellular interactions, including cell-cell and cell-matrix signaling. Tumor cell mutations, the release of specific signaling molecules, the capacity to withstand circulatory pressures, and signaling exchanges with target organs collectively govern the selective nature of organ-specific metastasis. Furthermore, factors intrinsic to the target organ-such as its regenerative potential, metabolic profile, immune surveillance mechanisms and matrix stiffness-further facilitate the adaptive remodeling of metastatic cells within these environments. Thus, the bidirectional selection and adaptation between tumor cells and target organs form a dynamic, complex system that reshapes our understanding of metastatic tumor development. While current research emphasizes shared biological features in metastasis, the successful formation of metastatic tumors depends not only on these common mechanisms but also on the unique characteristics governing organ-specific metastasis. The interplay between generalizable and organ-specific mechanisms profoundly influences the metastatic outcome. This review aimed to consolidate our current knowledge of these shared and distinct processes, analyze the evolving understanding of the bidirectional selection between tumor cells and target organs, and assess the current status of metastatic risk prediction models for patients without metastasis. Furthermore, the paper discussed the challenges and opportunities in managing advanced-stage metastatic tumors, offering new insights and potential clinical strategies to improve prognosis and treatment outcomes.